Updating a physiography-based soil map using digital soil mapping techniques - Bedendo, Dante Julian; Schulz, Guillermo; Olmedo, Guillermo Federico; Rodriguez, Dario Martin; Angelini, Marcos Esteban (Springer, 2024)
Research work carried out in Entre-Rios province(Argentina) for mixed land use planning and management in relation to suitable soil conditions required high-resolution soil information at farm level. Basic information was provided by a 1:20000 scale soil map made using physiographic analysis with intensive aerial photo-interpretation of soil-landscape relationships and landscape-||oriented field survey. Continuous productivity - index (PI) classes were predicted from a nu8mber of environmental covariates, mostly DEM derivatives, using regression and geostatistical techniques.The PI land classification was used to adjust the soil-landscape/soil-series interpretation of the existing choropleth soil map by means of correlating discretePI values obtained from a conventional mapping procedure with cpntinuous PI values obtained by soil digital mapping procedures.